Australian transnational vocational education : imperatives, challenges and improvements for curriculum implementation - (:unkn) unknown (Springer, 2024)
"This book explores questions about the relevance of implementing curriculum in transnational vocational education, in situations where teachers are expected to maintain standards in a country for which it was not designed. It provides a situational model of curriculum implementation that explains the complexity of factors that influence teachers’ enactment of the curriculum and how they engage in decision-making, problem-solving, and curriculum formation to overcome the constraints associated with implementation in transnational settings. It also proposes five improvements for strengthening the relevance, quality, and sustainability of transnational vocational education and the worth of vocational qualifications obtained by students internationally. This book serves as a helpful resource for teachers, curriculum developers, policymakers, educational managers, sponsors, students, regulators, academics, and anyone with an interest in transnational education, curriculum implementation, and/or teacher decision-making, as it provides a situational model of curriculum implementation and practical strategies for improving transnational programs in different teaching and learning contexts." (Publisher, BIBB-Doku)
E-Book für BIBB-Mitarbeitende über die Bibliothek erhältlich.
Keywords: P 3.2 Lehrpersonal; L 1 Curricula & Lehrpläne; I 2.3.5 Australien, Ozeanien; 370; Berufsbildung; Lehrerbildung; Curriculum; Implementation; Curriculumentwicklung; Australien